Are There Effects of Brand Equity Elements at Hospital Wirahusada Kisaran - Hamsi, Quratul Aini; Girsang, Ermi; Nasution, Sri Lestari Ramadhani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Brand equity will make it easier for the hospital to market and determine the patient's wishes. This research is to find out how the Brand Equity Elements at RSU Wira Husada Kisaran. The sample size in this study was 20 samples. Research time was conducted since the author surveyed in January 2022 until data collection, followed by a seminar on results. The results showed that only the brand loyalty variable did not affect the interest of patients in reusing Wira Husada Kisaran Hospital, for variables brand awareness, perceived quality, association, word of mouth, and marketing mix affect the patient's interest in reusing Wira Husada Kisaran Hospital. The suggestion is that RSU Wira Husada Kisaran should optimize patient satisfaction and meet patient needs by adding health services that are to patient needs and improving service quality.is the new face of Turkey under Erdogan's political management